Ethnobotanical assessment of medicinal plants in the ecosystems of the Nurata Range, using an integrated approach - Kosimov, Zokir; Khabibullaev, Bekhruz; Beshko, Natalya; Bussmann, Rainer; Akbarov, Feruz (Ethnobotany Research and Applications, 2026)
Background: Medicinal plants play an essential role in traditional healthcare systems; however, their ethnobotanical importance is often assessed using single-parameter approaches that do not fully reflect their multifunctional value. Integrated evaluation frameworks are therefore required to provide a more comprehensive assessment of medicinal plant resources at the regional scale. Methods: Ethnobotanical data were obtained from an original database comprising 374 medicinal plant species traditionally used in Uzbekistan. Based on clearly defined selection criteria, 110 species directly associated with the ecosystems of the Nurata Range were selected for analysis. An integrated Ethnobotanical Value Index (EVI) was applied, incorporating five parameters: use diversity, chemical composition richness, diversity of utilized plant parts, diversity of preparation and application methods, and additional functional value. All parameters were standardized and equally weighted. Results: The calculated EVI values revealed a clear differentiation in ethnobotanical importance among the studied species. Twelve species (11%) were classified as low-value, 46 species (42%) as medium-value, and 52 species (47%) as high-value medicinal plants. Species with high EVI values were characterized by broad use diversity, functional versatility, and high practical adaptability. Based on EVI rankings, the top 20 medicinal plant species were identified as priority ethnobotanical resources in the Nurata Range. Conclusions: The results demonstrate that the integrated ethnobotanical evaluation approach is effective for assessing medicinal plant importance at the regional level. This framework enables the identification of both widely used and less-studied species with high applied potential and provides a solid methodological basis for conservation prioritization, sustainable use of medicinal plant resources, and future comparative ethnobotanical studies. Keywords: medicinal plants; ethnobotany; Ethnobotanical Value Index (EVI); integrated assessment; Nurata Range; biodiversity; traditional medicine